Efficiency optimization of an interleaved buck-boost converter with wide operation range - Jin, Shuhan (Nanyang Technological University, 2023)
Improving the efficiency of DC/DC converters has been a widely researched topic. This dissertation focuses on the investigation of bidirectional interleaved DC/DC converters, which exhibit higher efficiency compared to traditional single-phase DC/DC converters. However, these bidirectional converters often suffer from lower efficiency under light load conditions. To address this issue, two advanced control methods, namely Discontinuous Conduction Mode Control (DCM) and Variable Frequency Control (VF), are adopted as alternatives to Continuous Conduction Mode (CCM) to enhance the converter's efficiency. To compare the efficiency of these three methods, power loss calculations are performed, and power loss decomposition is carried out to derive four types of loss analysis models. The power loss calculations are conducted under six different light load conditions, allowing for a comprehensive comparison of efficiency in each case to determine the optimal control method. The accuracy of the conclusions is validated by demonstrating a high level of consistency between the model calculations and Simulink simulation results. By conducting this study, the most effective control method can be identified to enhance the efficiency of bidirectional interleaved parallel DC/DC converters under various load conditions.